Une lecture d’une esthétique de la rivalité par la sémiotique situationnelle - Lambert Lipoubou; Marie Danay Vinguedassalom (Communication)
This article uses the situational semiotics of process communications, which deals with the construction of meanings by actors, to analyze an exchange at a bus stop between a group of friends, a blind person and her guide dog. Analysis reveals the in-act communication activities of "womanizing", "rivalry" and "hostility." This study is set within the field of rivalry phenomenology, according to which the object of conquest leads to conducts of challenge and duel and thus focuses on the aesthetics of rivalry that sets up the instrumentalization of desire.